Numerical simulations of a conceptual blade cooling with a working medium - Rogoziński, Krzysztof; Nowak, Grzegorz (Computer Assisted Methods in Engineering and Science, 2017)
The development of steam power units aims to increase the working steam parameters as they are the main factors that determine the efficiency of energy conversion. Most state of the art units are designed for supercritical steam parameters. However, the temperature level of steam feeding the turbine is limited by thermal strength of the material used to make the machine components. In this situation, using nickel alloys or cooling the elements exposed to the impact of high temperatures could be the appropriate solution. The former is rather expensive and the latter - technically difficult. The cooling option would require that the cooled element should be fed by a steam with a very high pressure and with a lower temperature than the temperature in the machine flow system. This paper presents the concept of using working steam as the cooling medium after it is expanded in a convergent-divergent nozzle. In such a case, the cooling system is very simple and the performed simulations indicate, for example, that the turbine blades may be cooled in this way.